2023
DOI: 10.1177/00346446221094867
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Policy and Monetary Integration in the Ecowas

Abstract: Those with dissenting view regarding the structure of monetary union arrangement in ECOWAS often argue that the macroeconomic convergence criteria have hampered the ability of countries in the region to stabilize their economies with appropriate counter-cyclical fiscal policy. We test the empirical merit of this assertion and found no support for this view. Instead, discretionary fiscal policy has actually become counter-cyclical in ECOWAS after the introduction of convergence criteria. In specifics, we found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The results revealed that the union has not led to income convergence within the CFA bloc. Onye and Umoh (2023) explored the role of fiscal policy in forming a union in ECOWAS. The paper found that fiscal policy is important in the discussions of a monetary union as fiscal policy operations became countercyclical in the formation of a union post-convergence era between 2003 and 2018 compared to the pre-convergence era between 1995 and 2002.…”
Section: Empirical Issues On Monetary Integrationmentioning
confidence: 99%
“…The results revealed that the union has not led to income convergence within the CFA bloc. Onye and Umoh (2023) explored the role of fiscal policy in forming a union in ECOWAS. The paper found that fiscal policy is important in the discussions of a monetary union as fiscal policy operations became countercyclical in the formation of a union post-convergence era between 2003 and 2018 compared to the pre-convergence era between 1995 and 2002.…”
Section: Empirical Issues On Monetary Integrationmentioning
confidence: 99%
“…However, the possibility of uniform monetary policy has been hampered by differences in the system structure of member states, lack of macroeconomic performance convergence, and the staggering effect of the political struggle of various degrees (Onye and Umoh, 2021).…”
Section: Introductionmentioning
confidence: 99%